Internationalize? Why? - Motivations of Portuguese firms - Lobo, Carla Azevedo (2020)
Business internationalization has become in recent decades, more than a requirement, a strategy of many firms, regardless their size or age. Besides trying to reach new markets and new clients, internationalization has turned into a strategy of the organization itself, far beyond its need to survive. Several authors highlight the company's growth strategies, in which facing the difficulty of growing in the national market given the increased competition, the public policies restricting business expansion, among others, the company chooses to go international and take advantage of the opportunities created in a new market. The Dunning model (1992) was based on four motivational factors: resource-seeking, market-seeking, efficiency-seeking and strategic asset-seeking. Although this typology was an important reference to explain the motivations for international expansion of multinationals from developed countries, empirical evidence has shown that the motivations of smaller companies can be quite different. Accordingly, some studies make a more extensive and complementary proposal. They suggest that there are two types of factors: the reactive and the mixed factos, that can influence the strategic management of internationalization. Reactive motivations include internationalization by drag and the imperatives of the business itself. At mixed motivations, authors consider, for example, geographical proximity and cultural affinities, the advantage of economies of scale, the use of the country's image and also government support. The reasons underlying the decision of firms' internationalization may therefore have different segmentations, and may well differ when it comes to SMEs or large firms. This work aims to identify the determinants that motivated the internationalization decision of portuguese firms, namely to understand whether they adopt a reactive or more proactive approach, that we can naturally associate with a strategy of reaction to, for instance, the retraction of internal demand, or a more active strategy that is part of the new mission or vision of the company. It will also be tried to ascertain whether there are any diferences in the most frequent motivations between the smallest and the largest companies. To achieve this goal we will use Quantitative Analysis Methodologies, through Descriptive and Inferential Analysis. Data were collected from 238 valid responses questionnaire and were treated by IBM SPSS Statistics 24.0 software. Our preliminar results show that the most important determinants for internationalization are in line with those defined by the Dunning model, despite the size or age of the firm.